Concept, features and types of corruption - L. I. Kalienichenko; D. V. Slynko (Law and Safety)
Corruption is a negative dynamic objectively existing social phenomenon, which necessitates its constant research in order to create new, change existing mechanisms for its detection, prevention and counteraction. In the process of working on a scientific article, such general scientific methods as hermeneutic and classification method were used. The hermeneutic method was used during the analysis of the etymological meaning of the term corruption and certain provisions of international legal acts, the Law of Ukraine “On Prevention of Corruption”. The method of classification was used in the process of dividing the concept of “corruption” into types. Among the special scientific methods logical-semantic and logical-legal were used. They allowed us to formulate the main features of corruption as a legal phenomenon.